Daily Bul and Co. - Balthazar, André; Bury, Pol; De Croës, Catherine; Fondation Maeght, Saint-Paul de Vence; Studio Passage 44, Brussel (Brussel : Ministerie van de Franse Cultuur, 1976)
Adami, Valerio ; Alechinsky, Pierre ; Baal, Frederic ; Baj, Enrico ; Balthazar, André ; Vautier, Ben ; Bertholo, René ; Brusse, Mark ; Bryen, Camille ; Bury, Pol ; Calder, Alexander ; Calderara, Antonio ; etc
+ bijlage in nederlands
Daily Bul and Co, Fondation Maeght, Saint-Paul de Vence, 7 februari - 7 maart 1976 / Studio Passage 44, Brussel, 9 april - 23 mei 1976
boek